Hubungan Antara Komunikasi Pembelajaran dengan Hasil Belajar pada Pembelajaran Daring Program Kesetaraan Paket C di SPNF SKB Sidoarjo - Nuratmila Rosada Janah; Heryanto Susilo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
Achieving good learning outcomes will be obtained through planning a mature online learning process, one of which is learning communication. This study aims to find out how big the relationship between learning communication is with learning outcomes in online learning. The research method used was a quantitative approach with a comparative causal research type and a sample of 27, namely package C class 12 students. Data was collected through questionnaires, tests, observation, and documentation techniques. The results showed that the relationship between learning communication and learning outcomes in sociology subjects had a sig (1-tailed) score of 0.282, English subjects had a sig (1-tailed) score of 0.271, the civics education subject showed a sig (1-tailed) value of 0.262 , then for the Indonesian language subject with a sig (1-tailed) score of 0.132, and in the mathematics subject a sig (1-tailed) score of 0.337. So it can be interpreted that there is no significant relationship between learning communication and learning outcomes in online learning for the package C equivalence program at SPNF SKB Sidoarjo.